Analisis Penguasaan Konsep Fisika Materi dan Perubahannya Melalui Penyelesaian Soal Isomorfik pada Siswa Kelas VII MTS Zainul Bahar - Alivia, Haniyah; Wahyudianti, Ratih; Hidayati, Hidayati; Imaniyah, Kamilatul; Prastowo, Sri Handono Budi (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2023)
The number of students who do not master physics learning, especially in the material and its changes. In this case, there are various abstract concepts which result in students having difficulties and confusion in learning and understanding concepts. The purpose of this research is to analyze the mastery of the concept of material physics and its changes through solving isomorphic questions in class VII students of MTs Zainul Bahar. This research is included in the type of descriptive research in which by analyzing students' mastery of concepts related to the material and its changes. As many as 25 students in class VII Mts Zainul Bahar, the method used is to give isomorphic questions as many as 10 multiple choice type questions. The results that have been obtained show that students' mastery of physics concepts related to material and its changes through isomorphic questions is very good with a percentage of 81%, while students who lack mastery of material concepts and their changes are as much as 19%. So that by going through isomorphic questions it is proven that students can increase their understanding and mastery of the material and its changes, and are motivated to improve student learning outcomes.